Electrical characteristics of doped ZnOCu2O heterojunction diode by sputtering method - Abd Rahman, A.B.; Alias, Afishah; Shain, F.L.; Lam, W.Y.; Mohamad, K.A. (akademisains, 2018)
Heterojunction thin films made from the combination of oxide semiconductor have attracted much attention due to its wide range of functional properties and plenty of potential application in optical and electronic devices. Zinc oxide (ZnO) semiconductor gains interest due to its versatile characteristics with wide direct band gap of 3.37 eV with added advantages to be used as in optoelectronics devices. In this paper, the electrical performances of heterojunction n-type ZnO (n-ZnO) and p-type cuprous oxide (p-Cu2O) diodes will be compared with Al doped ZnO/Cu2O and Ga doped ZnO/Cu2O diodes. Heterojunction nZnO/p-Cu2O diodes were fabricated by RF sputtering method. Pure ZnO ceramic target with 99.99% purity used as material target for ZnO thin films. A mixture of 3 wt% Al2O3 with 97 wt% ZnO and a mixture of 3 wt% Ga2O3 with 97 wt% ZnO used as target material for doped ZnO thin films. Several measurements such as resistivity, I-V curve, threshold voltage, series resistance and diode ideality factor were investigated. The overall results suggest that the doped heterojunction n-ZnO/p-Cu2O diodes perform far better as compared to pure n-ZnO/pCu2O.